Correction: Antibacterial Activity and Mechanism of a Scorpion Venom Peptide Derivative In Vitro and In Vivo. - Luyang Cao; Chao Dai; Zhongjie Li; Zheng Fan; Yu Song; Yingliang Wu; Zhijian Cao; Wenxin Li (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0040135.].